Evaluating the taxonomy of macrofossils used in macroevolution: a case study of Artemisia (Asteraceae) - Jiao, Bo-Han; Lu, Li-Li; Chen, Chen; Wei, Meng; Shen, Jia-Hao; Yuan, Yuan; Wang, Yu-Fei; Gao, Tian-Gang (Phytotaxa, 2022)
Fossils recorded information of the past phenotype and geographic distribution directly. Incorporating fossils information into phylogenies of living taxa would deepen our understanding of their macroevolution. Accurate taxonomy of these fossils is the first step before employing them. However, the taxonomy of some fossils has not been evaluated carefully. Here we take Artemisia as an example. We investigated the morphology of all the available Artemisia macrofossils based on the latest phylogeny and evaluated their taxonomic identities by comparing them with extant representative species. Our result showed that the taxonomic identities of these macrofossils are doubted. They would better not be treated as members of Artemisia for subsequent phylogenetic or biogeographic studies. This study improves our knowledge of the morphology of Artemisia, highlights the importance of careful morphological comparisons between fossils and living taxa, and reveals that attention should be given to the uncertainty of the fossil taxonomy.